Measurement of information system maturity at PT Bee solution partner using the SAMM method - Dila, Syafika Zalfanissa; Pramudita, Helmy; Abdillah, Alfina Poetri; Maharani, Rifqah Haura; Rofif, Rizky Muhammad (Jurnal Mandiri IT, 2024)
This research aims to analyze the level of alignment between business strategy and information technology strategy at PT Bee Solution Partner using the Luftman method. PT Bee Solution Partner, an information technology company located in Arcamanik, Bandung, provides bootcamp services, consultations, and overseas development, as well as IT consulting for application creation. The data collection method used is a closed questionnaire, structured with predetermined answer alternatives. The research results indicate that PT Bee Solution Partner has achieved aligment between business and IT strategies at level 4 (improved/managed process) according to the Luftman method. At this level, the organization is assesed to be strong in aligning IT and business, with the business considering IT to add value and being willing to take risks and benefits arising from the use of IT. The research conclusion indicates that overall, PT Bee Solution Partner has reached a fully strategic position at level 5 according to the Luftman method. However, there are some aspects of each criterion that need improvement to enhance the maturity of aligment between business and IT strategies. These the findings provide additional insights into the steps that can be taken to strengthen the integration of business and IT strategies in the context of an Information Technology company. This research is expected to contribute to a better understanding of the importance of aligning business and IT strategies in optimzing the performance of Information Technology companies.